The efficacy of transnasal palatal transillumination for the diagnosis of submucous cleft palate - Yasir S. Jamal; Sabah S. Moshref; Abeer M. Baamir; Mazin O. Kurdi; Doaa Y. Jamal (SpringerOpen, 2021)
Abstract Background Submucous cleft palate (SMCP) is a congenital abnormality with various clinical and anatomical features. Submucous cleft pathologies may be unrecognized during routine examinations. Current diagnostic techniques are constrained and unrevealing in presurgical patients. This prospective study aimed to evaluate transnasal palatal transillumination technique in diagnosis of SMCP at our institute hospital, during period from 2005-2020. Patients and methods Twenty-one cases with SMCP were recruited with age range from 2-60 months. Transnasal palatal transillumination with controllable light intensity endoscope used to evaluate SMCP and cases were photo and video recorded. Results In this study, 21 cases (13 males and 8 females) with SMCP were detected or confirmed by intranasal transnasal palatal transillumination. Frequency of SMCP patients at our institute was 3.39%. All patients presented with symptomatic complaints at diagnosis time, apart from 5 patients (23.8%) were diagnosed during cleft lip repair operations. Presenting symptoms were hypernasality (23.8%), delayed speech (23.8%), perforated palate with nasal escape of milk and food (14.3%), feeding difficulties (14.3%), and otitis media (4.8%). During intra-oral examination, all cases had a bifid uvula accompanied SMCP. Submucous cleft palate appeared as thin palate with central lucency. According to operative findings, operations done for repair were mostly two long palatal flaps (n = 13, 61.9%), von Langenbeck (n = 5, 23.8%), simple repair with lateral release incisions (n = 2, 9.6%), and simple repair without lateral release incision (n = 1, 4.8%). Conclusions Intraoperative assessment of submucous cleft palate with transnasal palatal transillumination is easy and cheap method to avoid missing cases of SMCP.